2008
DOI: 10.4049/jimmunol.180.10.6518
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Ig and Mucin Domain-1-Mediated T Cell Activation Requires Recruitment and Activation of Phosphoinositide 3-Kinase

Abstract: Ligation of the transmembrane protein T cell Ig and mucin domain (Tim)-1 can costimulate T cell activation. Agonistic Abs to Tim-1 are also capable of inducing T cell activation without additional stimuli. However, little is known about the biochemical mechanisms underlying T cell stimulation or costimulation through Tim-1. We show that a tyrosine in Tim-1 becomes phosphorylated in a lck-dependent manner, whereupon it can directly recruit p85 adaptor subunits of PI3K. This results in PI3K activation, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 43 publications
9
92
0
Order By: Relevance
“…This finding is reminiscent of previous work on another Tim family member, Tim-1. For example, we showed that Tim-1 also requires proximal T-cell receptor signaling machinery in order to activate NFAT/AP-1 (13). In addition, it has been reported that in human T cells, Tim-1 can be cocapped with the TCR/CD3 complex (5).…”
Section: Discussionmentioning
confidence: 93%
“…This finding is reminiscent of previous work on another Tim family member, Tim-1. For example, we showed that Tim-1 also requires proximal T-cell receptor signaling machinery in order to activate NFAT/AP-1 (13). In addition, it has been reported that in human T cells, Tim-1 can be cocapped with the TCR/CD3 complex (5).…”
Section: Discussionmentioning
confidence: 93%
“…Unlike TIM-1 and TIM-3, TIM-4 does not have a known signaling motif in its cytoplasmic tail (30,(53)(54)(55)(56). Additionally, TIM-4-mediated engulfment of apoptotic cells has been shown not to involve the ELMO1/DOCK180/Rac or GULP signaling pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…Kim-1 is known to directly interact with phosphatidylinositol-3-kinase (PI3K) pathway subunit p85 and regulate PI3K signaling in a phosphotyrosinedependent manner. 42 Recently, we demonstrated that Kim-1 interaction with p85 and subsequent PI3K-dependent signaling pathway play an important role in kidney injury and repair. 37,43 The PI3K/AKT/mTOR pathway is a well known intracellular signaling pathway related to cell growth, proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%